Application of Cavalieri Method on Measurement of Brain Haemorrhage Volume of Stroke Patients - Ety Sari Handayani (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
In stroke, CT Scan is a standard gold examination to distinguish infarction from bleeding. The stereology principle of the Cavalieri method has been used in several studies that calculate the volume of ischemia and the volume of bleeding in the radiological photos of stroke patients. The availability of stereology software in Indonesia is still limited. Measurement of the volume of ischemia of the brain is still using a manual way that is with a grid of points. The accuracy of this technique still needs to be proven. This study aims to find out the accuracy of cavalieri method in measuring the volume of brain hemorrhage in CT Scan photos of stroke patients. The study consisted of two groups. Group A is the volume of bleeding that comes from CT scan photos without the Cavalieri method. Group B is the volume of bleeding derived from CT scan photos with the Cavalieri method. The difference in bleeding volume was analyzed using t-test. The results of the study did not differ in measuring the volume of bleeding between the CT Scan method and the Cavalieri method (p > 0.05). This indicates that the result of measuring the volume of bleeding by Cavalieri method is the same as the measurement result using CT Scan.